Pengaruh Pemberian Silase Pakan Komplit Berbasis Sorgum dan Clitoria ternatea dengan Penambahan Konsentrat Mengandung ZnSO4 dan Zn-CU Isoleusinat Terhadap Konsumsi, Kecernaan Protein Kasar dan Retensi Nitrogen Kambing Kacang - Doko, Hendrik; Hartati, Erna; Jelantik, I Gusti N.; Oematan, Gustaf (Animal Agricultura, 2024)
The purpose of this study was to evaluate the effects of feeding sorghum-Clitoria ternatea-based complete feed silage with additional concentrates containing ZnSO4 and Zn-Cu Isoleucinate at different levels on consumption, crude protein digestibility, and nitrogen retention of Peanut goats. A total of 12 Peanut goats with an average weight of 13.19 kg were used in this study using a Randomized Group Design (RAK) with 4 treatments and 3 replications. Results showed that silage feed with 150 mg ZnSO4/kg BK ration and 2% Zn-Cu Isoleucinate/kg BK concentrate significantly affected crude protein consumption and digestibility, and nitrogen retention. The addition of concentrate up to 30% was the best treatment.